Study on the effect of activated coal gangue on the mechanical and hydration properties of cement - Zhu, Zewen; Liu, Chaoqun; Mao, Lin; Han, Zhixing; Chen, Leiwei; Zou, Huijie; Li, Lianghua; Yu, Pengfei; Dong, Jingliang; Zhang, Yonggang (Frontiers in Materials, 2023)
This study aims to minimize the carbon emissions of cement and investigate the viability of employing activated coal gangue (CG) as an additional cementitious ingredient. This paper investigated the effects of water-cement ratio, ages, and amount of activated CG dosing on the compressive and flexural strength of cement mortar as well as the effects of activated CG on hydration products, hydration process, and hydration degree. The impacts of activated CG on the hydration products and microstructure of cement were examined using XRD, SEM, and TG/DTG systems. A large amount of active SiO2 and Al2O3 in the activated CG react with Ca(OH)2 leading to a secondary hydration reaction in cement. The hydrated calcium silicate and hydrated calcium aluminate gels produced by the subsequent hydration process can reduce the porosity of hardened cement and boost cement mortar strength. The 28 days flexural and compressive strengths of specimens with 30wt.% activated CG rise by 11.69% and 11.82%, respectively, in comparison to that of specimens with 30wt.% quartz powder. When activated CG is mixed with cement, the early hydration rate of the cement can be decreased while the later hydration rate is increased.